Part A:
4x + 2(x − 3) = 4x + 2x − 11
4x + 2x - 6 = 4x + 2x - 11
6x - 6 = 6x - 11
Subtracting 6x from both sides:
-6 = -11
Since -6 does not equal -11, there are no solutions to this equation.
Part B: I used the Distributive Property to simplify the equation.
An equation is shown below:
4x + 2(x − 3) = 4x + 2x − 11
Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points)
Part B: Name one property you used to solve this equation. (4 points)
Please explain in 1 sentence
1 answer